DAMPAK PERKEMBANGAN PEMUKIMAN PADA HUTAN MANGROVE TERHADAP KEBERADAAN DAN FUNGSI MANGROVE DI DESA GENTING PULUR KECAMATAN JEMAJA TIMUR KABUPATEN KEPULAUAN ANAMBAS - Kusuma, Fira (2015)
Pesatnyaperkembanganpemukimanpendudukmengakibatkanberkurangnya areal hutanbakau (Mangrove) baiksecarakuantitasmaupunkualitasnya, danselanjutnyamempengaruhifungsiekosistemmangrove di PulauJemajaKabupatenKepulauanAnambas.Hutanmangrovemerupakansebuahekosistempantaidanpesisir yang memilikifungsikhusus. Banyakfaktormenjadipenyebabmenurunnyaeksistensihutan mangrove baikfaktorfisisdanfaktorsosial.Penelitianinibertujuanmengetahuibagaimanaperkembanganpermukimansebagaifaktorsosial yang mempengaruhikeberadaandanfungsi mangrove.Metodepenelitian yang digunakanyaitukuantitatifdenganpendekatansurveimelaluiwawancarakepadamasyarakatdanobservasi di kawasanhutan mangrove desaGentingPulur. Hasilpenelitianmenunjukkanbahwaberkembangnyapemukiman di desaGentingPulurmempengaruhikeberadaandanfungsidarihutanmangrove. Perkembanganpemukimanmemilikiindikatorsepertiluaspemukiman, jumlahrumah, danpertumbuhanpenduduk.Berdasarkanhasilujiregresi linier sederhanapertumbuhanpendudukmenjadifaktor yang paling dominanmempengaruhiluashutan mangrove disebabkanolehangkapertumbuhanpenduduk yang tinggidesaGentingPulursetiaptahunnyamencapai 3,95 % yang beradadiatas rata-rata pertumbuhanpenduduknasionalyaitu 1,5 %/tahun. Bertambahnyapendudukberhubungandengankondisisosialekonomimasyarakat yang turutmempengaruhikeberadaandanfungsihutan mangrove.Pemerintahperlumengendalikanlajupertumbuhanpendudukdengan program pengendalianpenduduk, hutan mangrove dapatdijadikanusahaekonomikreatifmasyarakatuntukmenambahpendapatantentunyahutan mangrove harustetapdilestarikandengancaramenjadikankawasan mangrove sebagaikawasanekowisatasupayafungsifisisdanbiologistetapterjaga. Sedangkanfungsiekonomispenggunaankayubakardarihutanmangroveharusdapatdikurangi, agar ekosistemmangrovemenjadisumberdayaalam yang berkelanjutan. Kata Kunci :Pemukiman, Keberadaan, Fungsi, hutanMangrove The rapid development of settlement areas result in reduced mangrove forest both in quantity and quality, and further affected the function of the mangrove ecosystem on the Jemaja island Anambas Island Regency. The mangrove forest is a beach and coastal ecosystems that have special functions. There are many factors cause the decline of mangrove forests existence, both physical factors and social factors. This study aims to determine how the residential development as social factors that influence the existence and function of the mangrove. The research method used is quantitative research with survey method by interviewing to the societies and the observation in the area of mangrove forests in GentingPulur village. The result of research show that the settlement development in GentingPulur village affects the existence and function of the mangrove forests. The settlement development has an indicators such assettlement area, the number of houses, and population growth. Based on the results of simple linear regression test indicates that population growth becomes the most dominant factor affects the mangrove forest area in consequence of the high population growth rate of PulurGenting village every year reach 3.95%, which is above the average growth of the national population, that ia 1,5%/years. The increasing of population related with socio-economic conditions of society that affect the existence and function of the mangrove forest. Governments need to control the population growth rate by population control program, mangrove forests can be used as a creative economy business for society to increase the income, which certanily mangrove forests should still be preserved by making the mangrove areas as ecotourism in order to the physical and biological function is maintained. While the economical function of firewood use from mangrove forests must be reduced, so that mangrove ecosystems become sustainable natural resources. Keywords: Settlement, existence, function, Mangrove forest